High inspired CO2 target accuracy in mechanical ventilation and spontaneous breathing using the Additional CO2 method - Magnusson, Gustav; Engström, Maria; Georgiopoulos, Charalampos; Cedersund, Gunnar; Tobieson, Lovisa; Tisell, Anders (Frontiers in Medicine, 2024)
ABSTRACT Background: Cerebrovascular Reactivity Imaging (CVR) is a diagnostic method for assessment of alterations in cerebral blood flow in response to a controlled vascular stimulus. The principal utility is the capacity to evaluate the cerebrovascular reserve, thereby elucidating autoregulatory functioning. In CVR, CO2 gas challenge is the most prevalent method, which elicits a vascular response by alterations in inspired CO2 concentrations. While several systems have been proposed in the literature, only a limited number have been devised to operate in tandem with mechanical ventilation, thus constraining the majority CVR investigations to spontaneously breathing individuals. Methods: We have developed a new method, denoted Additional CO2, designed to enable CO2 challenge in ventilators. The central idea is the introduction of an additional flow of highly concentrated CO2 into the respiratory circuit, as opposed to administration of the entire gas mixture from a reservoir. By monitoring the main respiratory gas flow emanating from the ventilator, the CO2 concentration in the inspired gas can be manipulated by adjusting the proportion of additional CO2. We evaluated the efficacy of this approach in 1) a ventilator coupled with a test lung and 2) in spontaneously breathing healthy subjects. The method was evaluated by assessment of the precision in attaining target inspired CO2 levels and examination of its performance within a magnetic resonance imaging environment. Results & Discussion: Our investigations revealed that the Additional CO2 method consistently achieved a high degree of accuracy in reaching target inspired CO2 levels in both mechanical ventilation and spontaneous breathing. We anticipate that these findings will lay the groundwork for a broader implementation of CVR assessments in mechanically ventilated patients.